Analisis Ketepatan Pengukur Daya dan Faktor Daya Listrik Berbasis Arduino Uno R3 328P - Wilda Noer Agustianingsih; Paulus Setiawan; Freddy Kurniawan (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2021)
Electric power and power factor are two parameters that must be considered because they involve the quality of the energy consumed. In order to be able to analyze these, a microcontroller-based power and power factor meter are needed which can be further developed. In this research, a power and power factor meter based on the ATmega328P microcontroller was developed on the Arduino board. Several algorithms are used to calculate the frequency of the grids, as well as the true-RMS of voltage and current. The simulation results show that this system can measure the power and power factor for input voltages of 100 to 300 volts with a frequency of 45 to 156 Hz for loads up to 5 amperes. The mean calculation average error for linear load is 0.28% for active power and -0.33% for apparent power. Meanwhile, for nonlinear loads, the calculation average error for active power is 1.86% and apparent power is 0.47%.